Study of local diffusion coefficients of the hydration layer of lipid vesicle bilayers - Kausik, Ravinath; Armstrong, Brandon D.; Han, Songi (Diffusion Fundamentals, 2009)
Water molecules near the surface of vesicle bilayers exhibit slow dynamics with respect to that of pure bulk water as they belong to the hydration layer. We present a unique analysis tool for the selective detection of local water of the hydration layer on the surface of unilamellar vesicles and the determination of its diffusion coefficients. We utilized stable nitroxide radicals covalently attached to the hydrophilic head groups of DOPC lipid chains that incorporate along with other lipids into vesicles. Through the use of dynamic nuclear polarization (DNP) the 1H NMR signal of local water interacting with the radical is amplified, and we present here an analysis of the local diffusion coefficients of this hydration layer.